THE INFLUENCE OF THE INTERNATIONAL STANDARD ISO 10015:2019 DIMENSIONS ON ORGANIZATIONAL EFFECTIVENESS THROUGH THE MEDIATING ROLE OF ADMINISTRATIVE EMPOWERMENT: AN ANALYTICAL STUDY IN THE MAYORALTY OF BAGHDAD (American Journal of Business Management, Economics and Banking, 2024)
The current study aims to determine the influence of the dimensions of the international standard ISO 10015:2019, represented by its provisions (competence management, competence management, and individual development) on organizational effectiveness through the mediating role of administrative empowerment in the Mayoralty of Baghdad, where the study is applied. The study seeks to diagnose the extent of the Mayoralty of Baghdad's awareness of the standard's requirements: International and the extent of its interest in levels of administrative empowerment and interest in organizational effectiveness. The researcher used the descriptive and analytical approach, using the questionnaire to collect data and information. A sample that included 380 was selected and distributed among department directors, assistant department directors, and division and unit officials at the upper and middle administrative levels. The Executive Office at the headquarters of the Baghdad Mayoralty, where it is applied, and SEM (structural equation modeling) statistical methods were adopted to achieve the study's objectives. To diagnose and measure the study variables and test the study hypotheses, reliance was placed on statistical applications (SPSS 27), in addition to the statistical package (STATA 17) and the statistical package (R), and the study reached a set of conclusions, the most important of which is the existence of a relationship and impact to the dimensions of the international standard ISO 10015:2019 in organizational effectiveness, and that administrative empowerment achieves mediation between the variables of the study. The study also reached a set of recommendations, the most important of which is the necessity of establishing the Baghdad Mayoralty, Conducting an evaluation survey and measuring the effectiveness of applying the competency management and personnel development system by the international standard ISO 10015:2019 so that empirical evidence of the results of applying this standard is obtained, and working to restructure personnel development programs in a way that helps to use competence within the organization in a more effective and focused manner. In addition to working on monitoring and evaluating the personnel development program and its implementation by competent observers.